Heterogeneous distribution of polycyclic aromatic hydrocarbons in surface sediments and red mullet along the Spanish Mediterranean coast - León, V.M.; García, I.; Martínez-Gómez, C.; Campillo, J.A.; Benedicto, J. (Marine pollution bulletin, 2014)
PAHs distribution in surface sediments (μgkg−1d.w.) in Valencia (2006 and 2007). [Display omitted] •Spatial PAH distribution was heterogeneous in the majority of coastal sediments.•Higher PAH concentrations in sediments were detected close to hotspots.•PAH levels were lower than EACs except in sediments from Barcelona and Sagunto.•3 Ring PAHs were predominant in red mullet and 4–5 ring PAHs in sediment.•PAH levels in sediment were only correlated with TOC or fine fraction in some areas. The spatial distribution of polycyclic aromatic hydrocarbon (PAH) concentrations was characterised in surface sediments and red mullet from eleven Iberian Mediterranean coastal areas. Mean PAH concentrations ranged from 28 to 1006 and from 3 to 40μgkg−1d.w. in sediment and red mullet muscle, respectively. The highest PAH concentrations in sediments were detected close to main ports and urban nuclei. However, concentrations of PAHs in red mullet showed little correspondence with PAH concentrations of the sediments due to its metabolic capacity. Phenanthrene was the predominant homologue in red mullet, whereas fluoranthene, pyrene and benzo(b)fluoranthene were the most abundant ones in sediments. Significant correlations between PAHs and organic carbon or fine fraction in sediments were only found in some areas. PAH concentrations in sediments were lower than environmental criteria in the majority of cases, except for benzo(g,h,i)perylene in 25% of samples from the Barcelona coastal area and for several homologues close to the port of Sagunto.